Performance Analysis of Direct Methanol Fuel Cell for Optimal Operation - Cho, Changhwan; Kim, Yongchan; Chang, Young-Soo (JAPAN SOC MECHANICAL ENGINEERS, 2009)
Direct methanol fuel cell ( DMFC) is one of promising candidates for power sources of mobile devices. Efficient operation of fuel cell system is very important for long-sustained power supply due to limited tank size. It is necessary to investigate performance characteristics of the fuel cell stack for efficient control of the DMFC system. We have developed an electrochemical model of DMFC using experimental data. The generated voltage is modeled according to various operating conditions; methanol concentration, cell temperature, and load current. The crossover phenomenon is also included in cell model. The model fits the experimental data well within 10 percent error. It is found that the efficiency of the fuel cell is mainly dependent on concentration of the methanol solution. Maximum efficiency line exists at specific concentrations of methanol solution with respect to the amount of generated power. Also efficient control method of the stack is presented.
Keywords: DMFC; SYSTEM; PEMFC; POWER